2018
DOI: 10.2147/cia.s170111
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between bone turnover markers, serum magnesium and bone mass density in postmenopausal osteoporosis

Abstract: IntroductionBone mass density (BMD) is still the gold standard for the diagnosis of osteoporosis, but bone turnover markers (BTMs) can provide helpful information regarding the bone remodeling process. The aim of this study was to determine the correlations between BMD and serum levels of BTMs (tartrate-resistant acid phosphatase-5b [TRAP-5b]), bone-specific alkaline phosphatase (BSAP), estradiol (E2), and magnesium (Mg[2+]) ion concentrations in postmenopausal osteoporotic women as compared to healthy postmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
2
41
0
3
Order By: Relevance
“…Twenty articles were included for full-text assessment, from which 9 were excluded from the sample studies: two did not have data on serum Mg; four mentioned osteoporosis, but their main target was osteoporotic fractures; two involved patients administered with drugs that improved the concentration of serum Mg|; one compared the concentration of serum Mg between osteoporosis and osteopenia. We included a total of 11 eligible papers, representing 2,776 postmenopausal women from 16 case-control studies [ Figure 1 ; ( 6 , 8 , 23 31 )]. Among them, according to the age and the location of measurement, Okyay's study ( 26 ) was divided into six part.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty articles were included for full-text assessment, from which 9 were excluded from the sample studies: two did not have data on serum Mg; four mentioned osteoporosis, but their main target was osteoporotic fractures; two involved patients administered with drugs that improved the concentration of serum Mg|; one compared the concentration of serum Mg between osteoporosis and osteopenia. We included a total of 11 eligible papers, representing 2,776 postmenopausal women from 16 case-control studies [ Figure 1 ; ( 6 , 8 , 23 31 )]. Among them, according to the age and the location of measurement, Okyay's study ( 26 ) was divided into six part.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has demonstrated that bone mass in diabetic patients is significantly decreased, and the risk of fracture is increased (24). Estrogen reduction significantly increases the risk of OP (25,26). E2 the most potent estrogen; however, its role in diabetes-related OP is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this TRACP5b is accepted as a marker of both: the number of osteoclasts and their activity [48,49]. It presents low diurnal variability and is not affected by feeding [50], being typically increased in high bone turnover conditions [51]. There are specific immunoassays for serum TRACP5b detection, actually it has been proposed for the evaluation of BMD in women [52].…”
Section: Tartrate-resistant Acid Phosphatase (Tracp5b or Trap5b)mentioning
confidence: 99%